Effect and Consequence e-Customer Satisfaction for e-Commerce Users - Patrada, Rolan; Andajani, Erna (Institut Teknologi Sepuluh Nopember, 2020)
The 4.0 industrial revolution has changed people's behavior to use everything through technology. This happens also in terms of shopping that can be done by many people through e-commerce. This study aims to examine the effect of online convenience, website design, security, information quality, and e-service quality on e-word of mouth, behavioral intentions, and e-loyalty through e-customer satisfaction respondents who use e-commerce to shop at Indonesia, especially Surabaya. The data used in this study are primary data obtained through distributing questionnaires to 205 respondents who are male and female e-commerce users, who are at least 15 years old, and have conducted transactions in e-commerce at least 5 times in the past year. The sampling technique in this study is non-probability sampling. This research uses a quantitative approach using statistical testing. The test was carried out using the Structural Equation Modeling (SEM) method with the SMART-PLS 3.0 program. The results of this study indicate that only online convenience, security, and information quality have an influence on other dependent variables through e-customer satisfaction, while website design and e-service quality have no effect